INITIAL EXPERIENCE OF LAPAROSCOPIC PARTIAL NEPHRECTOMY IN HASAN SADIKIN GENERAL HOSPITAL BANDUNG - Daniswara, Nanda; Pramod, Sawkar Vijay; Sibarani, Jupiter; Safriadi, Ferry (Indonesian Journal of Urology, 2016)
Objective: To describe our experience about laparoscopic partial nephrectomy to treat localized renal tumour patients in Urology Department Hasan Sadikin General Hospital Bandung. Material & method: In 2014, there were 6 female patients that underwent laparoscopic partial nephrectomy in Hasan Sadikin General Hospital Bandung. In one case, there were tumours on both kidneys. Five patients were underwent transperitoneal approach and 1 patient were undergo retroperitoneal approach. All patients were examined with ultrasonography and Abdominal CT scan with contrast. We also calculate RENAL nephrometry score. Results: There were 6 female patients with left flank pain that undergo laparoscopic partial nephrectomy. In one case, there are tumours on both kidneys. In RENAL nephrometry score calculation, there were 3 patients with 10x score, 1 patient with 11x score, 1 patient with 7x score, and 1 patient with 6p score. From all of them, 4 patients were successfully performed laparoscopic partial nephrectomy, 1 patients was undergo laparoscopic nephrectomyand 1 patient is converted to open partial nephrectomy. Five patients were undergo transperitoneal approach and 1 patient was undergo retroperitoneal approach. Surgery ranged from 180-240 minutes. Intra operative bleeding was ranged from 50-200 cc. Tramadol intravenous was used for post operative pain control. With VAS score in first post operative day was 6, and 2 at the time of discharge. Hospitalized time was ranged from 4-6 days. Conclusion: Laparoscopic partial nephrectomy is an alternative treatment that safe for localized renal tumour. This procedure is depend on the technique and approach from each Urologist. Our limitations are we didn’t have laparoscopic ultrasonography and the tumour close to pelvocalyces system.